2024
DOI: 10.1039/d3qo02071a
|View full text |Cite
|
Sign up to set email alerts
|

Ru(ii)-catalyzed regioselective [4 + 1] redox-neutral spirocyclization of aryl amidines with diazopyrazolones: direct access to spiro[indole-3,4′-pyrazol]-5′-ones

Bo Cui,
Jian Shen,
Yadong Feng
et al.

Abstract: An efficient protocol to construct spiro[indole-3,4'-pyrazol]-5'-ones via ruthenium(II)-catalyzed selective C-H bond activation/[4 + 1] spirocyclization starting from easily available N-aryl amidines and diazopyrazolones has been developed. A series of spiro-pyrazolones...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Cui, Lin and co-workers developed a Ru( ii )-catalyzed chemoselective and regioselective C–H acyivation/spirocyclization reaction to synthesize complex spirocycles products with distinctive structures. 36 The KIE results showed that the cleavage of the C–H bond might be the rate-determining step. Meanwhile, it is more straightforward to activate the C–H bond by connecting the electron-donating substituent in the aromatic ring (Scheme 23).…”
Section: Metal-catalyzed C–h Activation Of Amidines With Carbene Prec...mentioning
confidence: 99%
“…Cui, Lin and co-workers developed a Ru( ii )-catalyzed chemoselective and regioselective C–H acyivation/spirocyclization reaction to synthesize complex spirocycles products with distinctive structures. 36 The KIE results showed that the cleavage of the C–H bond might be the rate-determining step. Meanwhile, it is more straightforward to activate the C–H bond by connecting the electron-donating substituent in the aromatic ring (Scheme 23).…”
Section: Metal-catalyzed C–h Activation Of Amidines With Carbene Prec...mentioning
confidence: 99%